2021
DOI: 10.3390/s21217144
|View full text |Cite
|
Sign up to set email alerts
|

Human–Machine Differentiation in Speed and Separation Monitoring for Improved Efficiency in Human–Robot Collaboration

Abstract: Human–robot collaborative applications have been receiving increasing attention in industrial applications. The efficiency of the applications is often quite low compared to traditional robotic applications without human interaction. Especially for applications that use speed and separation monitoring, there is potential to increase the efficiency with a cost-effective and easy to implement method. In this paper, we proposed to add human–machine differentiation to the speed and separation monitoring in human–r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…These methods allowed for the continuous dynamic adjustment of the robot's speed. Novel research demonstrated a method for dynamically adjusting the protective separation distance, enabling the robot to operate at higher speeds by distinguishing between human and non-human entities using thermal imaging technologies [61]. Finally, another distinct research effort employed fuzzy logic to control a robot's speed by detecting the proximity and interaction velocity between robots and humans [62].…”
Section: Safety Standards For Collaborative Roboticsmentioning
confidence: 99%
See 1 more Smart Citation
“…These methods allowed for the continuous dynamic adjustment of the robot's speed. Novel research demonstrated a method for dynamically adjusting the protective separation distance, enabling the robot to operate at higher speeds by distinguishing between human and non-human entities using thermal imaging technologies [61]. Finally, another distinct research effort employed fuzzy logic to control a robot's speed by detecting the proximity and interaction velocity between robots and humans [62].…”
Section: Safety Standards For Collaborative Roboticsmentioning
confidence: 99%
“…The maximum safe speed threshold requested from the servo drives and the minimum protective separation distance that establishes their area of application must be pre-calculated according to ISO/TS 15066, and the risk assessment for the specific application [51,61]. Finally, considering the maximum velocity threshold value, the toolpath velocity override was selected so that none of the axes exceeded its individual velocity limit.…”
Section: Case 2: Simultaneous Application Of Sls and Toolpath Overridementioning
confidence: 99%
“…A wide variety of sensors can be encountered in the HRC-related literature, which can be positioned on a robot, on locations with a good view near the HRC workspace, sometimes even on a human. Commonly used sensors include the following: a single camera [7] or several cameras [8], stereo cameras [9], RGB-D visual sensors [10], ultrasonic sensors [11], infrared thermal sensors [12], laser-based technologies, including time-of-flight (TOF) sensor arrays, 3D TOF cameras and 2D/3D light detection and ranging (LiDAR) scanners [13][14][15][16], or different combinations, such as 2D laser scanners and a Kinect RGB-D visual sensor [17], or RGB cameras, a depth camera and a thermal imager [18].…”
Section: Introductionmentioning
confidence: 99%
“…These engineers will also need to design connected systems that can efficiently and safely interact with humans during the manufacturing process, e.g., a car assembly line [ 3 ]. The focal points of this Special Issue are the smart sensors that enable robots and humans to “see” each other [ 4 , 5 , 6 , 7 , 8 , 9 ] and the machine learning algorithms that process these complex data so the robot can make decisions [ 10 , 11 , 12 , 13 ].…”
mentioning
confidence: 99%
“…One limitation of using red–green–blue (RGB) imaging is the difficulty in distinguishing between humans in the foreground and moving objects in the background. Himmelsbach addressed this limitation in the field using thermal imaging [ 6 ]. This is especially advantageous for situations where robots can “see” both the operator’s workspace and walkways with roaming autonomous vehicles.…”
mentioning
confidence: 99%